The Manufacturing Of Cu-Al2O3 Composite Products: Study Of Process Parameters, Structure And Mechanical Properties - Sergei, Sapozhnikov (2016)
The purpose of this work is development of a method of producing the Cu-Al2O3 composite product by using the selective laser melting technology. The work includes 3 stages: production of composite powder, selective laser melting, mechanical tests of the obtained material. Method of production of composite powder has 2 stages: 1) production of metal powders by atomization of the liquid melt (Cu) in the gas jet, 2) modification of the surface of the metal particles of the second phase (Al2O3 nanopowder) in the planetary mixer. Metal powder was produced on URM-001 gas atomizer (patented by South-Ural State University). The surface modification of metal particles is produced in a planetary mixer KURABO Mazerustar kk250 with 5 different modes. Acceptable mode of modification is selected on the basis of the analysis of composite powders on a scanning electron microscope JSM-6400LV. The roundness of powders of Cu and Cu-Al2O3 determined using an optical analyzer OCCHIO 500. The conclusion is made about the suitability of powders for use in selective laser melting. The specimens of Cu and Cu-Al2O3 were made on the SINTERSTATION® Pro DM125 SLM machine by using different modes (power output, point distance, exposure time, hatch space). Surface end volume energy densities were used for describe of SLM modes. The structure of the composite material (Cu-Al2O3) using the chemical mapping was investigated on scanning electron microscopy. The mechanical tests on samples of Cu and Cu-Al2O3 made on the GLEEBLE 3800 Thermal-Mechanical Testing system.